Socialization Of Community Participation In Bandar Khalifah Village Development Planning Percut Sei Tuan District - Lukman Nasution; Abd. Rasyid Syamsuri; Reza Nurul Ichsan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
The results of observations of the main problems regarding to the activities or socialize participation community programs in the development planning of the Bandar Khalifa village, Percut Sei Tuan district include: a) The people of Bandar Khalifah Village, Percut Sei Tuan District, do not have knowledge about village development planning. b) The people in Bandar Khalifah Village, Percut Sei Tuan District, do not understand the participation activities that can be conducted by them in the village development planning. This activity was conducted in Bandar Khalifah Village, Percut Sei Tuan District in June, 2021. This socialization activity involved village heads and the community in Bandar Khalifah Village, Percut Sei Tuan District and hopefully the participants will be able to implement village development planning activities to encourage sustainable achievements. The conclusions obtained from the results of community service activities in Bandar Khalifah Village, Percut Sei Tuan District are: a) There is a material conformity with the needs of the community to understand the socialization of community participation in village development planning. b) There is a positive response from the community which is shown through discussions in terms of achieving village development planning in Bandar Khalifah Village, Percut Sei Tuan District.